Assessing the adoption and impact of genomics research at the Canadian Forest Service - Emily S. Hope; Debby C. Barsi; Daniel W. McKenney (The Forestry Chronicle)
The outcomes and impacts of government scientific research are difficult to evaluate, yet there is a growing demand for quantification of these impacts. Forest and forestry-related research is no exception. We adapted an impact assessment methodology for the evaluation of eleven ongoing forestry-related genomics projects within the Canadian Forest Service. The assessment made use of two tools, a Desktop Analysis and a more comprehensive Project Review survey. Results of the assessments indicate that much of the research contributes to the fundamental knowledge of Canadian forests, but also produces short-term technological benefits, including enhanced methodologies for the protection of Canadian forests from invasive species. A full report is available at: https://cfs.nrcan.gc.ca/publications?id=38253 (English) and https://cfs.nrcan.gc.ca/publications?id=38254 (French).